The mononuclear phagocyte system - tissue resident macrophages: distribution and functions - Gordon, Siamon (Henry Stewart Talks, 2021)
History of macrophages, Phagocytosis, Receptors of macrophages, Macrophage differentiation and activation, Diverse populations of macrophages, The distribution and function of macrophages